Immuno-Oncotherapeutic Approaches in Advanced Hepatocellular Carcinoma - Park, Robin (Vaccines (Basel), 2020)
Advanced hepatocellular carcinoma has limited treatment options, but there has been extensive growth recently with cabozantinib, regorafenib, lenvatinib, nivolumab, atezolizumab, and bevacizumab, which are some of the treatments that have received FDA approval just over the last three years. Because HCC tumor microenvironment is potentially immunogenic and typically characterized by inflammation, immunotherapy has been proposed as a potential novel therapeutic approach, which has prompted studies in advanced HCC patients investigating various immune-therapeutic strategies such as CAR-T cell therapy, checkpoint inhibitors, and onco-vaccines. The anti-PD-1 checkpoint inhibitors nivolumab and pembrolizumab have been FDA approved as a second line treatment in patients who progressed or are intolerant to Sorafenib. To build up on the success of PD-1 monotherapy, combinatorial regimens with PD-1/PD-L1 inhibitors plus VEGF targeted agents have shown positive results in various malignancies including HCC. The combination of atezolizumab plus bevacizumab is the new addition to the HCC treatment armamentarium following a pivotal study that demonstrated an improvement in OS over frontline sorafenib. Other novel immune-based approaches and oncolytic viruses are in the early phases of clinical evaluation. These innovative approaches enhance the intensity of cancer-directed immune responses and will potentially impact the outlook of this aggressive disease.